Exploring the training philosophy and practical strategies of Chen Wenbing, the gold medal coach of Chinese weightlifting - Liu, Y.; Cheng, L.; Xu, J.; Wang, L.; Cheng, W. (International Journal of Sports Science & Coaching, 2025)
Summarizing the training concepts of elite coaches is an effective means to enrich sports training theory and enhance the coaching abilities of young coaches. Coach Chen Wenbing is one of the elite representatives in the international weightlifting community, with brilliant coaching achievements. This article uses expert interview and literature review methods to analyze Coach Chen Wenbing's training concepts and coaching strategies. The primary conclusions are as follows: (1) Drawing on the scientific control theory of strength training, the stationary control training theory of technical movements, and the personalized training theory, an overall training framework is constructed with the core concept of "athlete-centered". (2) The training feedback mechanism is developed based on modern monitoring tools, athletes` subjective feedback, and coaches` experiential input. (3) Constructing the training situation according to the situation during the competition. (4) Establish a robust disciplinary framework to monitor the training status of athletes. (5) Pay attention to the moral education of athletes in order to assist them in developing correct values and good character.